2022
DOI: 10.1101/2022.03.02.482641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Duplex Structure of SARM1 Octamers Induced by a New Inhibitor

Abstract: In recent years, there has been growing interest in SARM1 as a potential breakthrough drug target for treating various pathologies of axon degeneration. SARM1-mediated axon degeneration relies on its TIR domain NADase activity, but recent structural data suggest that the non-catalytic ARM domain could also serve as a pharmacological site as it has an allosteric inhibitory function. Here, we screened for synthetic small molecules that inhibit SARM1 by stabilizing the ARM-dependent inactive, compact octamer ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
(108 reference statements)
0
5
1
Order By: Relevance
“…Weak activating mutations were recently discovered in ALS cohorts, 45 , 46 most of which are located in the ARM domain. We found that while some hSARM1 mutations are too strong and others too weak, one mutation, V112I 26 , 45 (although a significant activation by this mutation was not observed 46 ), seems to inflict similar cell death level as ceTIR-1 in HEK293F ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Weak activating mutations were recently discovered in ALS cohorts, 45 , 46 most of which are located in the ARM domain. We found that while some hSARM1 mutations are too strong and others too weak, one mutation, V112I 26 , 45 (although a significant activation by this mutation was not observed 46 ), seems to inflict similar cell death level as ceTIR-1 in HEK293F ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 90%
“…NAM, a product of NADase activity ( Figure S2 ), inhibited ceTIR-1 ( Figure 3C ) as was previously demonstrated for hSARM1. 20 , 24 , 26 Notably, we found that the chemical structure of the reaction products ( Figure 3D ) is different between the two orthologs: hSARM1 generates about 90% ADPR and 10% cADPR, while ceTIR-1 yields nearly opposite ratios ( Figure 3D ). However, at high protein concentrations, the isolated TIR domain of ceTIR-1 (ceTIR-1 TIR ) ( Figure S7A ) can also produce substantial amounts of ADPR in addition to cADPR ( Figures 3D and S7B ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…They remain morphologically intact and physiologically active for months after injury (Bittner, 1988). Whether activated programmed axon degeneration i) fails to deplete NAD + as observed in C. elegans (Khazma et al, 2023), ii) is not engaged due to a tight posttranslational regulation (Murata et al, 2018), or iii) is absent remains to be determined. This long-term survival was first observed in crayfish motor axons (Hoy et al, 1967), and subsequently in various other nervous systems, including leeches (Muller & Carbonetto, 1979), earthworms (Birse & Bittner, 1976), crickets (Clark, 1976), crustaceans (Bittner, 1973), and mollusks (Murphy A.…”
Section: Introductionmentioning
confidence: 99%